Protocol for RNA extraction from glioblastoma cell-line-derived spheroids embedded in atelocollagen gel guided by real-time imaging - Fujita, Mayumi; Imadome, Kaori; Sato, Tetsuro; Hirakawa, Hirokazu; Kado, Junko; Yamagiri, Asako; Miura, Taichi; Kamimura, Satoshi (STAR protocols, 2025)
Microscopy advancements enable real-time imaging and analysis of cancer spheroids embedded in atelocollagen gel. Here, we present a protocol for extracting high-quality total RNA from 3D tumor spheroids embedded in atelocollagen gel, including spheroids and invading cells dispersed into surrounding gel. We describe steps for spheroid formation, gel embedding, live-cell imaging, and image analysis. We then detail procedures for collecting sufficient quantities of total RNA suitable for comprehensive transcriptome analysis. This approach advances transcriptome profiling in diverse 3D cultured samples. [Display omitted] •This protocol enables time-specific RNA extraction from 3D cancer spheroids in atelocollagen•Time-specific RNA extraction from 3D cancer spheroids is guided by real-time imaging•High-quality RNA is obtained from both spheroids and dispersed invading cells•The method advances transcriptomic profiling in physiologically relevant 3D models Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. Microscopy advancements enable real-time imaging and analysis of cancer spheroids embedded in atelocollagen gel. Here, we present a protocol for extracting high-quality total RNA from 3D tumor spheroids embedded in atelocollagen gel, including spheroids and invading cells dispersed into surrounding gel. We describe steps for spheroid formation, gel embedding, live-cell imaging, and image analysis. We then detail procedures for collecting sufficient quantities of total RNA suitable for comprehensive transcriptome analysis. This approach advances transcriptome profiling in diverse 3D cultured samples.